2003
DOI: 10.1074/jbc.m209861200
|View full text |Cite
|
Sign up to set email alerts
|

A Single Amino Acid Exchange Inverts Susceptibility of Related Receptor Tyrosine Kinases for the ATP Site Inhibitor STI-571

Abstract: The tyrosine kinase inhibitor STI-571 potently blocks BCR-Abl, platelet-derived growth factor (PDGF) ␣-and ␤-receptors, and c-Kit kinase activity. Flt3, a receptor tyrosine kinase closely related to PDGF receptors and c-Kit is, however, not inhibited by STI-571. Sequence alignments of different kinases and indications from the crystal structure of the STI-571 Abl kinase complex revealed amino acid residues that are probably crucial for this activity profile. It was predicted that Flt3 Phe-691 in the ␤5 strand … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
41
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 34 publications
0
41
0
Order By: Relevance
“…A similar phenomenon was observed for EGFR, FGFR, and PDGFR (Blencke et al 2004). On the other hand, changing Phe-691 to smaller threonine rendered FLT-3 kinase sensitive to Imatinib (Bohmer et al 2003). In contrast, three indolinone compounds were found to be insensitive to mutations of this particular residue, suggesting that this class of inhibitors may represent an exception to the rule (Blencke et al 2004).…”
Section: Activity Of Su5416 On Mutant Retmentioning
confidence: 99%
“…A similar phenomenon was observed for EGFR, FGFR, and PDGFR (Blencke et al 2004). On the other hand, changing Phe-691 to smaller threonine rendered FLT-3 kinase sensitive to Imatinib (Bohmer et al 2003). In contrast, three indolinone compounds were found to be insensitive to mutations of this particular residue, suggesting that this class of inhibitors may represent an exception to the rule (Blencke et al 2004).…”
Section: Activity Of Su5416 On Mutant Retmentioning
confidence: 99%
“…However, substitution of Phe-691 with threonine renders the receptor susceptible to the drug (IC 50 0.1-0.3 mM). 148 FLT3 inhibitors cause cell cycle arrest, inhibit proliferation, and induce apoptosis in a variety of FLT3-dependent cell lines. In a number of different studies, the FLT3 inhibitors displayed in Table 5 have been shown to be cytotoxic to the human leukemia-derived cell lines MV4-11, MOLM-13, MOLM-14, EOL-1, and SEMK2, all of which express constitutively activated FLT3.…”
Section: Flt3 Inhibitorsmentioning
confidence: 99%
“…Even though these compounds are all likely to fit into the ATP binding pocket of the receptor, some may do so via an induced fit mechanism (like the indolocarbazole staurosporine appears to do when binding to CSK), while others bind in a lock-and-key manner (such as imatinib binding to ABL). 147,148 Inferring from the situation with other drugs, FLT3 inhibitors may bind to the active, inactive, or transitional state of FLT3. Selectivity for FLT3 may be greatly influenced by differences in single amino-acid residues between different receptors.…”
Section: Flt3 Inhibitorsmentioning
confidence: 99%
“…Structural data suggest that Imatinib acts by blocking the BCR-ABL protein in an inactive conforma-tion (12,13 ), which prevents the transfer of phosphate from ATP to substrates and blocks the downstream signal transduction pathways (14 -16 ). It has been postulated that mutations within the ATP-binding site can prevent Imatinib from binding, either interrupting critical contact points between Imatinib and the protein or inducing a conformation to which Imatinib is unable to bind (17,18 ). Several mutations have been reported in association with the resistant phenotype, and most of them are well characterized in terms of their ability and degree to which they induce resistance (4,7,9,19,20 ).…”
mentioning
confidence: 99%